Bases valorativas da preocupação masculina com a aparência - Freires, Leogildo Alves (2013)
The current thesis aimed at knowing the value basis of male concern with appearance. To accomplish it, two empirical studies were conducted. Study 1 aimed at adapting a measure of male concerns with appearance (Adonis Complex Questionnaire - ACQ) and other vanity (Vanity Questionnaire - VQ) for the Brazilian context, knowing evidence of factorial validity and internal consistency. Participants were 211 students from a public university in João Pessoa (PB). All were male (100%) and the mean age was 22 years (sd = 5.58). The ACQ, after checking its semantics validity, discriminative power and factorability of the correlation matrix (having followed the criteria of Kaiser, Catell and Horn), presented structured in three components: esthetic concerns (α = 0.78), physic-sexual concerns (α = 0.71) and dedication to diet / exercise (α = 0.72). The three factors explained jointly 41% of the total variance. The VQ (after following the same procedures used for the ACQ) was structured in four components: physical concerns (α = 0.87), view concerns (α = 0.81), achievement concern (α = 0.79) and achievement view (α = 0.67), and the three factors together explained 57.3% of the total variance. Therefore, it was concluded that these results allowed gathering evidence of factorial validity and internal consistency of the measures employed. Study 2 aimed to confirm the factor structure of the ACQ and VQ, providing more robust psychometric evidence for such measures and identifying the human values that are associated/predict the male concern with appearance. Participants were 205 men attending bodybuilding gyms in João Pessoa (PB), with an mean age of 25 years (sd = 6.31), most were heterosexual(88.3%), and single (75%). They answered the ACQ, the VQ, the Basic Values Questionnaire (QVB), the Scale of Satisfaction with Life (ESV), the Rosenberg Self-Esteem Scale (RAS) and a Sociodemographic Questionnaire. The results of confirmatory factor analyzes (CFA), allowed to prove the three-factor structure of the ACQ and four-factor the of QV, both identified in Study 1, and presenting satisfactory indexes of goodness of fit and composite reliability (CC). The analyzes of Pearson correlation and multiple regression (stepwise) provided subsidies for the development of a theoretical model involving the promotion values and suprapersonal values explaining vanity and these, in turn, explaining the Adonis Complex. Overall, this model had adequate fit to the empirical data:  ² / df = 5.47, GFI = 0.99, AGFI = 0.95, CFI = 0.98 and RMSEA = 0.07. In conclusion, the proposed objectives have been achieved in this thesis, presenting a contribution to a field of study scarcely discussed and considered in Social Psychology: male concern with appearance.